Wrestling with Group Identity: Disability Activism and Direct Funding - Christine Kelly (Disability Studies Quarterly, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> With disability representing a diverse array of experiences and identities, it seems unlikely that advocacy groups would be able to agree on concrete policy issues. And yet, there does appear to be consensus in the global North on a number of topics. This paper explores one such example, advocacy around direct funding models of care in order to ask the question: What are the implications for the collective identity of a social movement when groups coalesce around very particular issues? I uncover the implicit identity underlying direct funding advocacy, and how mobilizing around this identity has lead to substantial success in terms of instituting direct funding programs. However, the identity does not ‘disappear’ when the programs are actualized, leading to the exclusion and marginalization of many individuals from both specific programs and social movements. This collective identity has significant consequences for disability movements in the global North, how disability is defined and at times it results in conservative political demands. This paper suggests that a ‘collective of individuals’ approach to conceptualizing and enacting social movements represented by Titchkosky (2003) and Do-It-Yourself feminism may hold potential for future disability activism.
Keywords: identity; direct funding; disability movement; disability activism; social movements; essentialism